History in the making - Elliott, J. H. (John Huxtable) (Yale University Press, 2012)
From the vantage point of nearly sixty years devoted to research and the writing of history, J.H. Elliott steps back from his work to consider the progress of historical scholarship. From his own experiences as a historian of Spain, Europe, and the Americas, he provides a deft and sharp analysis of the work that historians do and how the field has changed since the 1950s. The author begins by explaining the roots of his interest in Spain and its past, then analyzes the challenges of writing the history of a country other than one's own. In succeeding chapters he offers acute observations on such topics as the history of national and imperial decline, political history, biography, and art and cultural history. Elliott concludes with an assessment of changes in the approach to history over the past half-century, including the impact of digital technology, and argues that a comprehensive vision of the past remains essential. Professional historians, students of history, and those who read history for pleasure will find in Elliott's delightful book a new appreciation of what goes into the shaping of historical works and how those works in turn can shape the world of thought and action.